RELATIONSHIP BETWEEN FUNCTION AND PRESENCE AND TYPE OF DEFORMITY IN PATIENTS WITH CEREBRAL PALSY - Murilo Tavares Daher; Paulo Leandro Souza Martins; Adriano Passáglia Esperidião; Pedro Felisbino Júnior; Vinício Nunes Nascimento; José Humberto Pereira Júnior; André Luiz Passos Cardoso; Brenda Cristina Ribeiro Araújo; Sérgio Daher (Coluna/Columna)
ABSTRACT Objective: To evaluate the gross motor function (GMFCS) with respect to the prevalence and type of scoliosis in patients with cerebral palsy (CP). Methods: This was an analytical, cross-sectional study. We evaluated medical records and imaging studies of 100 patients randomly assigned to a specialist rehabilitation center for the care of such patients. The patients were classified according the gross motor function (GMFCS) and those with deformities were classified as per the kind of scoliosis through the classification of Lonstein and Akbarnia). A correlation was made among the presence of deformity, the variables of the type of deformity and motor function by GMFCS. Results: Of the 100 patients evaluated, 69 had scoliosis. The mean age of patients with scoliosis was higher than that of patients without deformity (12.63 and 10.46 years). Thirty-nine (57%) patients had spastic tetraparesis and 32 (46%) spastic diparesis. The most frequent curve pattern was the thoracolumbar and the average angular value of the main curve was 27 degrees. There was a positive correlation between the presence of scoliosis and GMFCS level V. There was also a positive correlation between the Lonstein Group II and GMFCS V. Conclusion: There is a positive correlation between the presence of scoliosis and greater involvement of gross motor function (GMFCS V). In patients with deformities, there is also a positive correlation between the Group II of Lonstein and GMFCS V.